The Relationship Of Knowledge And Attitude Of Pregnant Women With Audiovisual Promotion In Implementation Of Early Breastfeeding Initiation In Trimester Iii Pregnant Women In The Work Area Of The Simpang Dolok Puskesmas In 2021 - Herviza Wulandary Pane (Institute of Computer Science (IOCS), 2021)
Based on data from the Simpang Dolok Health Center, it was found that 3 out of 7 mothers stated that it was difficult and difficult to initiate early breastfeeding because of the mother's ignorance about early initiation of breastfeeding. The author assumes that this ignorance is due to the lack of counseling for pregnant women in the third trimester, ultimately mothers do not understand what IMD is, let alone how to apply it. The researcher believes that it is necessary to conduct counseling using the audiovisual method so that it is easy for mothers to understand the meaning of the counseling carried out by midwives or other health workers. Objective: to determine the relationship of knowledge and attitudes with the provision of audiovisual promotions with early initiation of breastfeeding in third trimester pregnant women in the work area of ​​Simpang Dolok Health Center in 2021. Methods: observational method that does not require treatment on the object of research with a cross sectional design. The primary data of the study were obtained from 50 populations. All populations were used as respondents (samples), complete sampling technique (total sampling), data collection by giving questionnaires of 5 questions of knowledge variable, 5 questions of attitude variable, 1 question of early initiation of breastfeeding. Processing of univariate and bivariate data with p-value (chi square) test with SPSS for windows version 17.0 statistical test tool. Results: the results obtained from the knowledge variable after audiovisual promotion of early initiation of breastfeeding through CD were samples with high knowledge who carried out early initiation of breastfeeding as many as 21 people (72.5%), moderate knowledge as many as 6 people (20.8%) and knowledgeable low as much as 2 people (6.7%). While the sample with high knowledge who did not carry out early initiation of breastfeeding were 9 people (42.8%), 8 people with moderate knowledge (38.1%) and 4 people with low knowledge (19.1%). From the attitude variable, there were 5 respondents who did not carry out early initiation of breastfeeding who behaved well (45.4%), 4 people behaved less (36.4%) and 2 people were not good (19.2%). Based on the P-value, obtained 0.003. Conclusion: the test where the P-value is 0.003 <0.05, so it can be seen that there is a significant relationship between the knowledge and attitudes of pregnant women with the provision of audiovisual promotion in the implementation of early initiation of breastfeeding for pregnant women in the third trimester in the work area of ​​the Simpang Dolok Public Health Center. 2021.